Evaluation of the durability performance of roller-compacted concrete incorporating recycled pavement materials - Ali Kouadri, Fadhila; Salhi, Mohamed; Boubekeur, Toufik; Benyahia, Amar; Li, Alex; Abbès, Boussad (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: This research investigates the durability of roller-compacted concrete pavement (RCCP) incorporating reclaimed asphalt pavement (RAP) as a partial or full replacement for natural aggregates  (NA). The primary objective is to assess the feasibility of using RAP in pavement concrete from both performance and sustainability perspectives.Methods: Concrete mixtures were prepared with four RAP substitution levels: 25%, 50%, 75%, and 100%. Durability tests were performed to evaluate the resistance of these mixes to acid and sulfate attacks. Additionally, microstructural analyses were conducted using scanning electron microscopy (SEM) and X-ray diffraction (XRD) to examine internal changes resulting from chemical exposure.Results: The incorporation of RAP improved durability against acid and sulfate attacks, particularly at substitution levels up to 50%. Beyond this threshold, a slight decline in performance was observed, though it remained within acceptable limits. SEM images revealed a denser matrix and stronger bonding between the cement paste and RAP aggregates. XRD analysis confirmed the presence of stable hydration products, even after exposure to aggressive solutions.Conclusion: The findings support the use of RAP as a viable and sustainable alternative to NA in RCCP. At optimal substitution levels, it enhances durability, contributes to environmental protection, reduces construction waste, and offers cost-effective solutions by utilizing recycled materials.
Keywords: roller-compacted concrete; recycled aggregates pavement; microstructure; durability